Survey of DC-DC non-isolated topologies for unidirectional power flow in fuel cell vehicles - Bhaskar M.S.; Ramachandaramurthy V.K.; Padmanaban S.; Blaabjerg F.; Ionel D.M.; Mitolo M.; Almakhles D. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost effectiveness; Electric load flow; Electric power transmission; Fuel cells; Topology; Vehicle transmissions; Automobile companies; Cost-effective solutions; Fuel cell vehicles; High power capacity; Prominent features; Renewable energies; State of the art; Vehicular applications; DC-DC converters